Um estudo de estimativa de fluxo e conjugado em motores de indução trifásicos implementação utilizando DSP - Severino, Públio Bernardes (2005)
This work presents a study and implementation of a torque estimator for three phase induction motors. Estimation is made from input voltages and currents and stator phase resistance is the only motor parameter needed. Torque estimation is obtained from stator flux estimation. This requires the integration of the phase counter electromotive force. An integration method able to avoid drifting and errors due to initial conditions is chosen and implemented. Torque estimator is implemented using a DSP board so that real time operation is possible. Experimental and simulated results are presented and found to be in good agreement.